The Social Problems of State Salary Policy of RA - Gyozalyan, Vardush (Bulletin of Yerevan University G: Economics, 2016)
The article covers the features and the main social problems in the sphere of state salary policy. In particular, the author accentuates the fact, that the minimal wage is not the sufficient guarantee to overcome the poverty line. The main flaws of the salary system in the sphere of state governance and public administration, and also the problems caused by the territorial and interbranch inequalities of the average salary are outlined.